Use of Telegram and cooperative learning in the teaching of scientific research in medical students - Matzumura-Kasano, Juan P. (2022)
Objective. To analyze the integration of the use of Telegram in cooperative learning as a teaching strategy for scientific research in medical students. Methods. Correlational, prospective research. The study population was made up of students from the research methodology course during 2021. A non-probabilistic sample of 68 students were used. Two instruments were used: Use of Telegram based on Tabrizi and Onvani criteria, with a reliability of 0,85, and the Cooperative Learning Questionnaire created by Fernández-Rio et al., with a reliability of 0,70. Data analysis was performed using SPSS. Results. 38 women and 30 men participated; the average age was 24.03 years. 82,4% used Telegram for the first time, 41,2% commented that the installation was very easy; 77,9% considered that the messages were pertinent; 39,7% stated it was easy to use and 29,4% perceived that communication improves. Use of Telegram in the personal dimension, 82,4% belong to the high level; in the learning and social dimensions, 72,1% and 89,7% correspond to the high level, respectively. Cooperative learning: In the dimensions, social skills, 91,2% belong to the achieved level; in group processing, 94,1% at the level achieved; in positive interdependence, 95,6% at the level achieved; in promoter interaction, 91,0% at the level achieved; and, in individual accountability, 97,1% at the level. The integration of Telegram use significantly influences in cooperative learning (Rho = 0,428). Conclusions. The use of Telegram was associated with an improvement in the teaching-learning process and greater cooperative work among the students participating in this research.